A strategy to improve electrochemical water oxidation of FeOOH by modulating the electronic structure. (December 2021) - Feng, Haopeng; Tang, Jing; Tang, Wangwang; Tang, Lin; Yu, Jiangfang; Wang, Jiajia; Yang, Yaya; Ni, Ting; Li, Chao; Luo, Jun
Highlights: P doping can weaken Fe-O bonds by forming P-O bonds. The adsorption energy of OER intermediates can be optimized. This strategy can optimize the electronic structure of FeOOH. The mechanism of enhanced OER activity is well explained. Abstract: The good performance of base metal oxides as alternative electrocatalysts for water oxidation has attracted great attention. However, the formed Fe-O bonds are not conducive to the dissociation of water molecule, which thus inhibit oxygen evolution reaction (OER). Herein, a facial on-site activation strategy is proposed to improve the OER activity of FeOOH by P doping. By optimizing the electronic structure, the obtained electrode exhibits an overpotential of 203 and 263 mV at 10 and 100 mA cm −2, respectively. Systematic experiments and theoretical analysis suggest that P doping can optimize the adsorption energy of OER intermediates by forming P-O bonds. Therefore, it enables P-FeOOH as a low-cost and efficient electrocatalyst and provides a strategy for designing new highly active and cost-effective catalysts for OER.